Pengaruh Kegiatan Menganyam Terhadap Konsentrasi Di Kelompok A TK Negeri Pembina Kota Selatan Gorontalo - Ardini, Pupung Puspa; Yusup , Saskiawati; Utoyo, Setiyo (Efektor, 2021)
The objective of this research was to examine the effect of weaving on a child’s concentration level. The research method was the experimental with pre-experimental design (one group pretest-posttest). The results of the research with 30 children as sample showed that there was difference between the average pretest and posttest. It can be seen in pretest obtained 15.97 and the standard deviation was 1.4735 while in posttest obtained 29.07 and standard deviation was 2.09981. These results proved that there is a significant influence before and after treatment. So, there is an influence of weaving activities on children's concentration.